Analisis Peningkatan Keselamatan Pada Perlintasan Sebidang Kereta Api Tanggulangin-Porong (Studi Kasus : JPL 75 KM 31+368) - Putra Iswanto, Ary; Diah Puspitasari, Mariana; Ahda Imron, Nanda; Via Dwi Mayangsari, Ayunda (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2022)
The railroad crossing is the intersection of a road with a railroad track. Accidents are the biggest problem at railroad crossings. Factors that cause accidents at railroad crossings, namely breaking through crossing gates, besides that the lack of safety facilities is one of the causes of accidents. To avoid this, it is necessary to review the improvement of safety at railroad crossings. This research on the JPL 75 KM 31+368 railroad crossing uses an analysis of calculating the average daily traffic volume multiplied by the volume of trains that pass, which is 85,407.5 smpk. These results already exceed the technical standard of railroad crossings, namely the volume daily traffic (LHR) is multiplied by the number of train trips that pass per day which is between 12,500-35,000 smpk, then the crossing does not need to be changed to a non-level crossing. Efforts to improve safety that need to be carried out by JPL 75 KM 31 + 368 from the direction of Kalitengah are in the form of safety signs in accordance with the guidelines of the technical standards of safety for a railroad crossing.